Taurine supplementation increases irisin levels after high intensity physical training in obese women - Batitucci, Gabriela [UNESP]; Cunha Brandao, Camila Fernanda; De Carvalho, Flavia Giolo; Marchini, Julio Sergio; Pfrimer, Karma; Ferrioli, Eduardo; Cunha, Fernando Queiroz; Papoti, Marcelo; Barros Morhy Terrazas, Sara Ivone [UNESP]; Junqueira-Franco, Marcia Varella Morandi; Ramos da Silva, Adelino Sanchez; Freitasa, Ellen Cristini de [UNESP] (Elsevier B.V., 2019)
Background: Irisin is a myokine/adipokine that under stimulus of physical exercise is able to improve thermogenic capacity in adipose tissue. Likewise, taurine supplementation has demonstrated similar effects on energy metabolism. Therefore, we hypothesized that taurine supplementation combined with physical training may induce an increase in irisin concentrations, optimizing energy metabolism in obese individuals. Objective: To evaluate if taurine supplementation associated with a high intensity physical training program increases irisin levels in obese women. Methods: double-blind study with 22 obese women (BMI 32.4 2.0 kg/m(2), 36.6 +/- 6.4 years and sedentary) who were randomly divided into two groups, control group (GC, n = 14), exercised and supplemented with placebo (3 g of starch), and taurine group (GTAU, n = 8), exercised and supplemented with taurine (3 g). The subjects performed high intensity physical training, Deep Water Running (DWR), for 8 weeks, 3 times/week, for 50 min per training session, at 70-85% maximum heart rate. Resting metabolic rate (RMR) was evaluated by indirect calorimetry, body composition by deuterium oxide, plasma taurine by HPLC, plasma irisin by Multiplex Kit, and food consumption by food records. The results were analyzed by an ANOVA two way repeated measures mixed model, with the Sidak post hoc (p < 0.05). Results: No changes were observed in body composition. DWR increased RMR independent of supplementation (p < 0.001) and irisin levels (pg/mL) showed a significant difference only in the GTAU in 1 h after exercise (p < 0.001). Conclusion: DWR associated with taurine supplementation resulted in increased plasma irisin concentrations after physical training in obese adult women.
Keywords: Obesity; Irisin; Taurine; Deep water running; Energy expenditure